Effect of feeding micronutrient fertilized sorghum hay based diet on nutrient utilization and mineral balance in sheep - DAS, M M; SINGH, K K; RAI, A K; MAHANTA, S K (The Indian Journal of Animal Sciences, 2018)
The present work was undertaken to study the effect of feeding micro-nutrient rich sorghum hay in the diet of sheep on nutrient intake and its utilization. Twelve adult Jalauni sheep (weighing 39.11±1.02 kg) were randomly divided into 2 groups of 6 animals each. The sheep of control group (G1) were fed on NPK fertilized chopped sorghum hay and crushed barley grain (300g/d) based ration, while the sheep of group G2 were offered NPK + 50% recommended dose of micronutrients (Zn, Mn and Cu 10, 5 and 2.5 kg/ha) + seed priming in 0.05% solution of ZnSO4 for 12 h + VAM inoculated sorghum hay along with barley grain (300g/d) for 30 days. Micro-nutrient (Cu, Zn and Mn) fertilization improved mineral content (ppm) in sorghum hay for Cu (7.47 vs 9.22), Zn (22.69 vs 27.48) and Mn (73.56 vs 102.01). The effective intake of minerals was Cu, 8.71and 10.06, Zn, 26.23 and 30.18; Mn, 62.59 and 86.05 ppm in G1and G2, respectively. The additional mineral supplementation through micronutrient rich sorghum hay had no significant effect on dry matter intake. Similarly, the intakes of digestible crude protein, metabolizable energy and digestibility of DM, CP, NDF, ADF, were also comparable among the groups. However, micro-nutrient (Cu, Zn and Mn) supplementation through fodder sorghum improved the mineral retention (Cu 2.84 vs 3.72 mg/d, Zn 11.72 vs 15.46 mg/d and Mn 26.19 vs 40.28 mg/d) without affecting significantly the absorption coefficient in adult sheep. The apparent absorption and retention of N was positive and comparable between thegroups. Nutrient content (%) in terms of DCP and TDN in both type diets fed to sheep were also similar. Thus, itÂ can be concluded that micro-nutrient (Cu, Zn and Mn) application to fodder sorghum improved the mineral content in the fodder, and feeding of micronutrient fertilized sorghum hay based diet improve the intake and retention of micro-minerals significantly without affecting nutrient intake and nutrient utilization in adult Jalauni sheep.